Blunt Pancreatic Injury in Major Trauma: Decision-Making between Nonoperative and Operative Treatment. (22nd February 2018) - Ull, Christopher; Bensch, Sebastian; Schildhauer, Thomas Armin; Swol, Justyna
Abstract : Blunt trauma injuries to the pancreas are rare but are associated with significant overall mortality and a high complication rate. Motor vehicle collisions are the leading cause of blunt pancreatic trauma, followed by falls, and sports injuries. We discuss the decision-making process used during the clinical courses of 3 patients with life-threatening blunt pancreatic injuries caused by traumatic falls. We also discuss the utility of the American Association for the Surgery of Trauma Organ Injury Scale (AAST-OIS), which provides a system for grading pancreatic trauma. Retrospectively, the cases reviewed were classified as AAST-OIS grade II, III, and IV in each one patient. Although the nonoperative approach was initially preferred, surgery was required in each case due to pseudocyst formation, pancreatic necrosis, and posttraumatic pancreatitis. In each case, complete healing was achieved through exploratory laparotomy with extensive lavage and placement of abdominal drains for several weeks postoperatively. These cases show that nonoperative management of pancreatic ductal trauma results in poor outcomes when initial therapy is less than optimal.